Effects of Lean Beef Intake, as Part of a Healthful Dietary Pattern, on Cardiometabolic Risk Markers in Subjects at Risk for Diabetes Mellitus: a Controlled Feeding Trial (FS18-02-19) - Maki, Kevin (Curr Dev Nutr, 2019)
OBJECTIVES: To assess and compare the effects of two diets low in saturated fatty acids (SFA): a United States Department of Agriculture (USDA) healthy US-style eating pattern (USDA diet) and a similar diet containing 150 g/d of lean beef in place of refined starches and added sugars (USDA-LB), on insulin sensitivity and other cardiometabolic markers in adults at-risk for type 2 diabetes (T2D). METHODS: This randomized, controlled crossover trial included two screening visits, a baseline visit, and two 28-d diet periods, separated by a 2-week washout. Thirty-three subjects (7 men, 26 women) provided evaluable data for this analysis. All foods were provided for each 28-d period. At baseline and at the end of each diet condition, insulin sensitivity and pancreatic beta-cell function were assessed with a 50-min intravenous glucose tolerance test. Other risk markers evaluated included fasting lipoprotein lipids, particles and subfractions, apolipoproteins A1 and B, homeostasis model assessment of fasting insulin sensitivity and beta-cell function, and high-sensitivity C-reactive protein. RESULTS: Baseline values and responses for selected variables are shown in the Table. Neither the USDA nor the USDA-LB diets had significant effects on insulin sensitivity or pancreatic beta-cell function; however, both produced a significant (P < 0.05) decrease in mean high-density lipoprotein cholesterol (HDL-C) versus baseline. The USDA diet also significantly (P < 0.05) reduced median non-HDL-C and mean total cholesterol (total-C) compared to baseline, but the response did not differ significantly from that of the USDA-LB diet. A shift toward larger and more buoyant LDL subfractions compared to the USDA diet (P = 0.007) and baseline (P < 0.05) occurred with the USDA-LB diet. No other significant differences were observed in carbohydrate or lipid metabolism and assessed parameters. CONCLUSIONS: Intake of a low-SFA, USDA healthy US-style diet lowered total-C, non-HDL-C, and HDL-C compared with baseline. Inclusion of 150 g/d of lean beef did not adversely affect insulin sensitivity and related cardiometabolic markers compared with the USDA healthy diet and produced a shift toward larger, more buoyant LDL subfractions. FUNDING SOURCES: Funded by The Beef Checkoff. SUPPORTING TABLES, IMAGES AND/OR GRAPHS: